Pengaruh Penilaian Kinerja Dan Kompensasi Terhadap Kinerja Karyawan Pada Unit Airport Rescue And Fire Fighting (ARFF) Pt. Angkasa Pura I Bandara Internasional Sultan Hasanuddin Makassar - Ibnu Abbas; Andi Nuryadin; Jumaidah Jumaidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Ibnu Abbas, 2024. The effect of job appraisal and compensation on employee performance at the airport rescue and fire fighting (ARFF) unit of PT Angkasa Pura I International Airport Sultan Hasanuddin Makassar. Thesis study programme of management science at STIM LPI Makassar (supervised by Dr Andi Nuryadin, S.E M.Si. and Jumaidah, S.Sos., M.Si.). This study aims to determine the effect of job appraisal and compensation on employee performance at the airport rescue and fire fighting (ARFF) unit of Angkasa Pura I International Airport Sultan Hasanuddin Makassar. The method used in this research using quantitative, quantitative method using primary data with a Likert measuring scale. Population 83 people. Sample 83 people using saturated samples. The results showed that there is a positive and significant effect of work appraisal and compensation on performance. on performance From the results of the study, conclusions can be drawn about the of the research conducted. Basically, employee performance always shows the process and results of the employee's work efforts. Work efforts that are born from the responsibilities of employees are carried out, but performance appraisal has a better impact than compensation or compensation. performance that has a better impact than compensation or in other words, employees in the ARFF PT. in other words, employees in ARFF PT Angkasa Pura I Makassar Branch.